Atividades de estudo e extensão realizadas no confinamento experimental da UNESP-Dracena - Assumpção, Alice Helena Peres Marques [UNESP]; Dellaqua, João Victor Tino [UNESP]; Sousa, Osvaldo Alex de [UNESP]; Santi, Pedro Fernando [UNESP]; Tomaz, Laís de Aquinoz [UNESP]; Santos, Anderson Augusto dos [UNESP]; Pinto, Leandro Dias [UNESP]; Bosco, Daniela Monte Serrat [UNESP]; Silva Filho, Wilson Inácio da [UNESP]; Pinto, Ana Carolina Janssen [UNESP]; Bertoldi, Gustavo Perina [UNESP]; Millen, Danilo Domingues [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The beef cattle is an activity in large expansion in Brazil, which is among the largest producers and exporters of beef in the world. With such production it is necessary to intensify it more and more, thereby ensuring its steady growth. Among the alternatives frequently used in intensive production is the feedlot, which allows producing more in a smaller area within a shorter period of time and using high-energy diets, thus, exploring the genetic potential of animals. With the increase of confined heads, surveys also multiply involving this system and a large part of these studies take place within universities, particularly in animal science courses. In order to deepen the studies on ruminant nutrition focused on beef cattle, the Center for Studies on Ruminants (NERU – abbreviation in Portuguese) promotes activities related to the area, with courses and symposia, lectures, expeditions and recently carrying out additional activities on experimental feedlot at the Experimental Campus of UNESP - Dracena. These activities involve the daily management within the confinement, with the weighing of excess, determination of dry matter, feces score, water dispenser cleaning, handling of consumption spreadsheet, observation of ingestive behavior, analysis of Penn State Particle Separator (PSPS) periodic weighing of animals, collection of feed and feces samples for laboratory testing, among other activities.

A bovinocultura é uma atividade em grande expansão no Brasil, que está entre os maiores produtores e exportadores de carne bovina do mundo. Com essa produção, é necessário intensificá-la mais e mais, garantindo assim seu crescimento constante. Entre as alternativas utilizadas frequentemente na produção intensiva está o confinamento, que permite produzir mais em uma área menor dentro de um período de tempo mais curto e usando dietas de alto valor energético, dessa maneira, explorando o potencial genético dos animais. Com o aumento de cabeças confinadas, as pesquisas também se multiplicaram envolvendo este sistema e uma grande parte desses estudos acontece dentro das universidades, particularmente em cursos de zootecnia. A fim de aprofundar os estudos sobre a nutrição de ruminantes focada em bovinos de corte, o Centro de Estudos de Ruminantes (NERU) promove atividades relacionadas com a área, com cursos e simpósios, palestras, expedições e recentemente atividades adicionais de confinamento experimental no Campus Experimental da UNESP - Dracena. Essas atividades envolvem a gestão diária do confinamento, com a pesagem de sobras, a determinação da matéria seca, o escore de fezes, a limpeza do bebedouro, a manipulação da planilha eletrônica de consumo, a observação do comportamento ingestivo, a análise da Penn State Particle Separator (PSP), a pesagem periódica dos animais, a coleta de amostras de alimentos e fezes para testes de laboratório, entre outras atividades.
Keywords: Extension; Feedlot; Beef cattle; Extensão; Confinamento; Gado de corte